2011
DOI: 10.1097/igc.0b013e31820b2df7
|View full text |Cite
|
Sign up to set email alerts
|

Low Colorectal Anastomosis After Pelvic Exenteration for Gynecologic Malignancies: Risk Factors Analysis for Leakage

Abstract: Objective:To study risk factors for low colorectal anastomotic leak after pelvic exenteration for gynecologic malignancies.Methods:Data from 60 patients, 32 with ovarian cancer and 28 with nonovarian cancer who underwent pelvic exenteration with colorectal anastomosis (CRA) were retrospectively analyzed.Results:Overall rate of CRA leak was 20%. The CRA leak was associated with type of tumor (3% for the ovarian cancer and 40.8% for the nonovarian cancer, P = 0.004), CRA height (<5 cm vs ≥5 cm, 75% vs 6.3%; P = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Some authors reported increased rate of morbidity in previously irradiated patients and reduced the amount of reconstructions in these patients. 10 In our series, we observed an overall major complication rate of 61% for the cohort with previous radiation treatment versus 33.5% for the entire cohort. This difference was not statistically significant probably because of the relative small numbers of complications, but the trend clearly shows an increased risk in previously irradiated patients.…”
Section: Discussionmentioning
confidence: 56%
“…Some authors reported increased rate of morbidity in previously irradiated patients and reduced the amount of reconstructions in these patients. 10 In our series, we observed an overall major complication rate of 61% for the cohort with previous radiation treatment versus 33.5% for the entire cohort. This difference was not statistically significant probably because of the relative small numbers of complications, but the trend clearly shows an increased risk in previously irradiated patients.…”
Section: Discussionmentioning
confidence: 56%
“…An unacceptable level of risk is observed when the colorectal anastomosis is set up at or under 5 cm from the anal verge. In these cases, a definitive colostomy should be recommended .…”
Section: Discussionmentioning
confidence: 99%
“…In cases of very low anterior resection (anastomosis within 6cm from the anal verge) the data suggest a potential benefit to drainage [16, 23, 28, 32]. Peeters et al concluded that pelvic drains may offer an earlier detection of AL [13] and Tsujinaka et al [36] suggested drains may help reduce the severity of consequences following an AL in colorectal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Significant improvements in outcome have been achieved by focusing on the refinement of surgical techniques and perioperative care. However, growing evidence from the colorectal [1, 2830] and the gynecologic oncology literature [13, 31–33] supports adaption of fast-track surgery to further enhance postoperative recovery and reduce morbidity. Such an approach warrants evaluating the utility of drains at time of LBR in OC.…”
Section: Introductionmentioning
confidence: 99%